Family and Bapas Class II Garut Collaboration in Strengthening Restorative Justice for Children in Conflict with the Law - Herlina, Elin; Andayani, Rini Hartini Rinda; Suyono, Sinta Yulianti; Nurusshobah, Silvia Fatmah (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
Children in conflict with the law require a justice approach that prioritizes protection, rehabilitation, and social reintegration rather than punishment. In Indonesia, restorative justice has been formally mandated through Law Number 11 of 2012 on the Juvenile Criminal Justice System, emphasizing the involvement of families and community institutions in resolving juvenile cases. This study aims to examine the collaboration between families and Bapas Class II Garut in strengthening restorative justice for children in conflict with the law. This research employed a qualitative descriptive approach and was conducted at Bapas Class II Garut, West Java. Data were collected through in-depth interviews with Community Counselors and family members, non-participant observation, and document analysis. The data were analyzed thematically to identify patterns related to forms of collaboration, supporting and inhibiting factors, and the impact of collaboration on children’s psychosocial recovery and social reintegration. The findings indicate that family–Bapas collaboration occurs across multiple stages, including social inquiry, diversion and restorative mediation, supervision, and post-resolution guidance. Effective collaboration is supported by the commitment of Community Counselors and strong family-oriented cultural values, while social stigma, limited legal awareness, economic constraints, and institutional limitations hinder sustained engagement. Importantly, collaboration contributes positively to children’s psychosocial recovery and social reintegration. This study concludes that institutionalizing family participation is essential to strengthening restorative justice and ensuring its transformative impact within Indonesia’s juvenile justice system.